Copper Ion Removal Using a Waste-Plastic-Derived Hydrogel Adsorbent Prepared via Microwave-Assisted PET Aminolysis - Kayee Chan; Masami Kawai; Mina Yamake; Anatoly Zinchenko (Gels, 2023)
Despite the tremendous progress in the development of functional materials from plastic waste to promote its recycling, only a few examples of hydrogel materials from plastic waste were reported. In this study, microwave-assisted depolymerization of waste PET plastic using polyamine was performed to prepare short aminophthalamide oligomers followed by chemically cross-linking into a hydrogel material. Catalyst-free microwave-assisted aminolysis of PET was completed within 30–40 s, demonstrating high efficiency of the depolymerization reaction. Subsequent epoxy cross-linking of the oligomers yielded a hydrogel with a swelling degree of ca. 92.1 times in pure water. The application of the obtained hydrogel for the removal of copper ions (Cu2+) from water was demonstrated. Efficient complexation of NH2 groups of the hydrogel with Cu2+ resulted in high adsorption capacities of the hydrogel material toward Cu2+ removal, which were the highest at neutral pHs and reached ca. 213 mg/g. The proposed type of environmental material is beneficial owing to its waste-derived nature and functionality that can be applied for the high-efficiency removal of a broad scope of known environmental pollutants.